Inquiries in the Economics of Aging. - Wise, David A. (National Bureau of Economic Research project report., 1998)
For over a decade, the National Bureau of Economic Research has sponsored the Economics of Aging Program, under the direction of David A. Wise. The program addresses issues that affect the well-being of individuals as they age and a society that is composed increasingly of older people. Within the next twenty years, an unprecedented proportion of Americans will be over sixty-five. New research in the economics of aging is an essential element of understanding what the future holds for this aging population. Inquiries in the Economics of Aging presents both empirical papers that consider questi.